Reducing emissions and air pollution from informal brick kilns: Evidence from Bangladesh - Brooks, Nina; Biswas, Debashish; Maithel, Sameer; Miller, Grant; Mahajan, Aprajit; Uddin, M. Rofi; Ahmed, Shoeb; Mahzab, Moogdho; Rahman, Mahbubur; Luby, Stephen P. (American Association for the Advancement of Science, 2025)
We present results from a randomized controlled trial in Bangladesh that introduced operational practices to improve energy efficiency and reduce emissions in 276 “zigzag” brick kilns. Of all intervention kilns, 65% adopted the improved practices. Treatment assignment reduced energy use by 10.5% ( P -value <0.001) and decreased CO 2 and PM 2.5 emissions by 171 and 0.45 metric tons, respectively, per kiln per year. Valuing the CO 2 reductions using a social cost of carbon of 185 USD per metric ton, we find that the social benefits outweigh costs by a factor of 65 to 1. The intervention, which required no new capital investment, also decreased fuel costs and increased brick quality. Our results demonstrate the potential for privately profitable, as well as publicly beneficial, improvements to address environmental problems in informal industries.